Study the Functions of Educational Vocational Guidance and Counselors in Government Schools of Delhi - Singh, Nahar; Kumar, Ashok (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
A study to assess the functions of Educational Vocational Guidance and counselors in govt. schools of Delhi was undertaken through a descriptive survey and document analysis. The study was conducted on 100 Educational and Vocational Guidance Counsellors (EVGCs) of govt. schools of Delhi with 60 respondents in all. A self-developed questionnaire and govt. documents were used to obtain data. Random sampling technique was used to select the sample for the study. The analysis done from the secondary data, the personal observations and the field visits done by the investigator, it is very clear that the EVGCs are not performing their roles and responsibilities properly, that is established by the govt. GNCT, Delhi. Therefore there is need to redefine these roles and responsibilities and principals should give help and proper time to performing their duties in schools.